2D electrical resistivity investigation at Ampar Tenang Landfill Site, Selangor D.E - Esmail Al-Sabahi ,; Abdul Rahim Samsuddin,; Wan Zuhairi Wan Yaacob ,; Umar Hamzah, (Universiti Kebangsaan Malaysia, 2008)
A 2D electrical resistivity survey was conducted to investigate the subsurface contamination underneath a domestic waste disposal site at Ampar Tenang, Dengkil, Selangor. The resistivity imaging technique was used in this study to locate the vertical and horizontal extend of contamination plumes underneath the site. A total of six 2-D resistivity imaging lines were established with two of them located outside the landfill area while one of them located in inactive landfill site. Another three lines were situated in the active landfill site. The results of the survey show that the resistivity value of the decomposed waste material in the inactive site of landfill is relatively low and the contaminated leachate plumes has low resistivity value of less than 2 Ωm. Characterisation of subsurface resisitivity and its relation to lithology was interpreted based on the available borehole data.